INNOVATIVE PEDAGOGICAL APPROACHES IN MALAYSIAN UNIVERSITIES: TRENDS AND CHALLENGES IN 21ST CENTURY LEARNING - Jaffery, Nur Shahafiqah Nadiah; Damit, Mohd Rozie Mohd; Hishamuddin, Mohd Razuan Abd; Syukur, Mohd Shahrizan; Datu Asal, Sharifah Sari; Abd Latif, Amir Abrar (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The 21st century has brought profound transformations to education, driven by rapid technological advancements, evolving pedagogical approaches, and shifting student expectations. In Malaysia, university education is continuously adapting to modern teaching strategies to equip students with essential skills for a highly competitive global workforce. This paper examines contemporary trends, challenges, and opportunities in Malaysian higher education, focusing on the integration of innovative pedagogical practices, digital learning tools, and policy frameworks. Key areas discovered include the impact of blended and online learning, the role of artificial intelligence in personalized education, and the effectiveness of competency-based learning models. Additionally, the study evaluates the influence of government initiatives and institutional policies on curriculum development and quality assurance. By analyzing these factors, the paper aims to provide valuable insights into effective educational strategies that enhance student engagement, foster critical thinking, and promote lifelong learning. The findings contribute to ongoing discussions on the future of higher education in Malaysia and offer recommendations for optimizing teaching methodologies to meet the demands of an evolving academic and professional landscape.